Serum creatinine as an indicator of lean body mass in vegetarians and omnivores - Bartholomae, Eric; Knurick, Jessica; Johnston, Carol S. (Frontiers in Nutrition, 2022)
Growing numbers of Americans are adopting vegetarian or vegan diets. While risk for some chronic conditions may be lower when following these diets, concern remains over the ability to consume adequate amounts of various nutrients, notably, protein. Knowing that serum creatinine is a reliable marker of muscle mass, this study examined the relationships between serum creatinine, lean body mass (LBM), handgrip strength, and protein intake in healthy vegetarian (n= 55) and omnivorous (n= 27) adults. Significantly higher protein intakes (+31%), LBM (+7%), serum creatinine (+12%) and handgrip strength (+14%) were observed for the omnivore participants compared to vegetarian participants. Positive correlations (p<0.001) were noted between creatinine and LBM (R2= 0.42), creatinine and handgrip strength (R2= 0.41), protein intake and LBM (R2= 0.29), and handgrip strength and LBM (R2= 0.69). These data show that serum creatinine concentrations were lower in vegetarian women and men in comparison to their omnivorous counterparts and that serum creatinine concentrations correlate with LBM and strength in healthy adults, regardless of diet.